Model of joint estimation and control of high speed and highly manoeurable aircrafts - Казак, В. Н. (Proceedings of National Aviation University, 2000)
Considered are problems of joint estimation and control of high speed and highly manoeurable aircrafts. Proposed is a solution of the problem of joint estimation and control of joint solution of Cauchy problem and two point boundary problem for differential equations in partial derivatives